Ризик-орієнтований підхід у сільському господарстві: поєднання технічного прогнозування та поведінкових моделей - Качула, Світлана Валентинівна; Kachula, Svitlana; Пашков, Олександр Геннадійович; Pashkov, Oleksandr (Чорноморський національний університет імені Петра Могили, 2025)
У статті розглянуто теоретичні засади ризик-орієнтованого підходу у сільському господарстві як одного із напрямків забезпечення стійкості аграрного виробництва в умовах зростання економічної, кліматичної та соціально-поведінкової невизначеності. Здійснено аналіз еволюції наукових поглядів на природу ризику та його роль у прийнятті управлінських рішень у сільському господарстві. Обґрунтовано доцільність інтеграції технічного прогнозування, заснованого на використанні даних, алгоритмів машинного навчання та кліматичних моделей, із поведінковими моделями, що враховують психологічні особливості прийняття рішень аграріями. Показано, що поєднання цих підходів формує основу для побудови комплексної системи управління аграрними ризиками, здатної адаптуватися до динамічних змін зовнішнього середовища. Результати дослідження сприяють розвитку теорії ризик-менеджменту в аграрному секторі та створенню методологічних передумов для подальших прикладних досліджень у сфері цифрової аналітики ризиків у сільському господарстві. The article provides a comprehensive theoretical exploration of the risk-oriented approach in agriculture as a key paradigm for strengthening the resilience, adaptability, and long-term sustainability of the agrarian sector amid intensifying economic volatility, environmental transformations, technological disruptions, and behavioral uncertainty. It highlights the historical evolution of the risk concept in economic theory and its transformation from a narrowly financial and statistical category into a complex interdisciplinary construct that unites technological, informational, ecological, social, and psychological dimensions. The study emphasizes that in modern agricultural systems, risk is not only a measurable probability of adverse outcomes but also a dynamic, multifactorial phenomenon shaped by decision-makers’ perceptions, experiences, and socio-economic contexts. Special attention is given to the synthesis of technical forecasting methods—encompassing data-driven analytics, artificial intelligence, machine learning algorithms, remote sensing technologies, and climate modeling—with behavioral models grounded in cognitive psychology and behavioral economics. Such integration allows for a deeper theoretical understanding of how agricultural producers perceive, assess, and respond to multiple sources of uncertainty, including market, production, and climate-related risks. The article underlines that the perception of risk in agriculture is often distorted by cognitive biases, emotional reactions, and social influences, which significantly affect the rationality of investment, production, and innovation decisions. Within this context, the risk-oriented approach is conceptualized as a holistic management framework that combines quantitative precision, algorithmic forecasting, and behavioral adaptability to enhance the accuracy of predictive models and the effectiveness of strategic responses to uncertainty. The theoretical outcomes of the study substantiate the necessity of developing new interdisciplinary frameworks that integrate digital technologies, predictive analytics, and behavioral insights into an adaptive model of agricultural risk management. The research contributes to the evolution of theoretical foundations of agrarian risk management and forms a methodological platform for future applied studies in digital risk analytics, decision sciences, and behavioral modeling within the context of sustainable agricultural development.
Risk-based approach in agriculture: combining technical forecasting and behavioral models
Keywords: ризик-орієнтований підхід; risk-oriented approach; сільське господарство; agriculture; технічне прогнозування; technical forecasting; поведінкові моделі; behavioral models; аграрні ризики; agrarian risks; управління невизначеністю; uncertainty management; цифрова аналітика; digital analytics